2012
DOI: 10.1097/rli.0b013e3182438e5d
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Diffusion Tensor Imaging of the Breast

Abstract: Mapping the diffusion tensor parameters at high spatial resolution provides a potential novel means for dissecting breast architecture. Parametric maps of λ1 and λ1-λ3 facilitate the detection and diagnosis of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
90
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 41 publications
13
90
1
Order By: Relevance
“…The changes in λ 1 were found to provide the highest contrast to noise ratio 19 . This study included 68 patients with confirmed pathology including 33 patients diagnosed with invasive ductal carcinoma (IDC), 19 with ductal carcinoma in situ (DCIS), 13 with invasive lobular carcinoma (ILC) and 3 with other malignancies.…”
Section: Representative Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The changes in λ 1 were found to provide the highest contrast to noise ratio 19 . This study included 68 patients with confirmed pathology including 33 patients diagnosed with invasive ductal carcinoma (IDC), 19 with ductal carcinoma in situ (DCIS), 13 with invasive lobular carcinoma (ILC) and 3 with other malignancies.…”
Section: Representative Resultsmentioning
confidence: 93%
“…More recently, diffusion weighted MRI and the resulting maps of apparent diffusion coefficient (ADC) have been evaluated as a complement method to DCE-MRI and it was shown that ADC values can help distinguish between cancers, benign lesions and normal breast tissue 9,10 . In addition, studies of breast diffusion tensor imaging (DTI) were initiated in healthy volunteers and patients with breast lesions at field strength of 1.5 T [11][12][13][14][15] and of 3 T [16][17][18][19][20][21][22][23][24] . Most of these studies reported ADC and fractional anisotropy (FA) values 11,12,14,15,[20][21][22][23] and found these two parameters to be reproducible with ADC values more reproducible than FA 13,20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, ROI is another influencing factor because of the heterogeneity of the breast tissue. 23,26,27 As for cellularity, tumour cells are not homogeneously distributed in the whole tumour. As is always the case, the ROIs in ADC and FA maps cannot be precisely corresponded to the FOVs for calculating the cellularity in the specimens; it will influence the evaluation of the correlation between ADC, FA and cellularity.…”
Section: Discussionmentioning
confidence: 99%